Glycine improves the remodeling process of tenocytes in vitro. (8th February 2018) - Vieira, Cristiano Pedrozo; Viola, Manuela; Carneiro, Giane Daniela; D'Angelo, Maria Luisa; Vicente, Cristina Pontes; Passi, Alberto; Pimentel, Edson Rosa
Abstract: Tendinitis changes the biochemical and morphological properties of the tendon, promoting an increase of activity of metalloproteinases and disorganization of collagen bundles. Tenocytes, the primary cells in tendon, are scattered throughout the collagenic fibers, and are responsible of tendon remodeling and tissue repair in pathological condition. In vivo, glycine, component of the typical Gly‐X‐Y collagen tripeptide, showed beneficial effects in biochemical and biomechanical properties of Achilles tendon with tendinitis. In this study, we analyzed the effect of glycine in tenocytes subjected to inflammation. Tenocytes from Achilles tendon of rats were treated with TNF‐α (10 ng/mL) with and without previous treatment with glycine (20 mM). Cell proliferation and migration were evaluated, as well as the expression of matrix molecules such as glycosaminoglycans, metalloproteinases (MMPs), TIMPs, and collagen I. Glycine can revert the inflammation due to the action of TNF‐α by controlling the MMPs quantity and activity. These data indicated that the molecules involved to remodeling process of extracellular matrix are modulated both by TNF‐α and the availability of collagen precursors; in fact, this study indicates the glycine can be useful for treatment of inflammation and for modulating tenocytes metabolism in tendons.